Evaluation of Osseointegration of Dental Implants Prepared by Piezosurgery (Clinical Study) - Jiheel, Younus Jabbar; mohammed, Jamal Abid (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Piezosurgery device is a system developed recently to overcome the limitation of the traditional surgical technique in implant site preparation, which use the principle of ultrasonic microvibrations to create precise & selective cut in bone in harmony with the surrounding tissues. The aim of this study was to evaluate the outcomes of implants inserted by ultrasonic implant site preparation protocol (UISP) using piezosurgery device, regarding the survival rate, stability and other related factors, at 16 weeks postoperative follow up period.Materials and Methods: A total of (24) patients, (6) males and (18) females, aged between (19-51) years old, contributed in this study receiving a total of (42) implants, all of these implants bed were prepared by means of special tips mounted in piezosurgery device. For each patient thorough clinical and radiographical preoperative assessment was applied. Implant stability quotient (ISQ) values were measured at baseline, 8 weeks and at 16 weeks. Postoperative clinical and radiographic evaluation was applied for each patient for 16 weeks postoperatively.Results: (24) patients received (42) implants accomplished the follow-up period, After 16 weeks all implants (42) were osseointegrated and the overall implants survival rate was 100% with no failure and no complication was observed. The mean ISQ value at baseline was (74.32±6.42), the mean ISQ value at 8 weeks was (72.62±9.05) and at 16 weeks the mean ISQ (±SD) value was (76.68±7.35) the changes in the mean stability during the healing period showed significant increase in the implant stability (P≤0.05). At the 16th week the number of implants that achieved ISQ≥70 was 35 (83.3%), and 7 implants attained ISQ> 70 (16.7%).Conclusions: high and significant survival rate, significant secondary stability, early positive shifting of the mean ISQ value, no remarkable complications in implants inserted by ultrasonic implant site preparation indicated that piezosurgery is a reliable alternative and safe method used in dental implant osteotomy.